PROFIL KETERAMPILAN SOSIAL SISWA DILIHAT DARI STATUS PEKERJAAN ORANGTUA (AYAH DAN IBU) SMP NEGERI 32 PEKANBARU - Adek Ayu Sakinah; Rosmawati Rosmawati; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
t others, cooperate, tolerate without sacrificing her talents, interests, values andpersonality. The ability of such students will make them more acceptable in their socialenvironment and allow individuals to interact with positive responses. The fact that thestudents found in SMP Negeri 4 Pekanbaru have not been able to develop their socialskills with the maximum. This factor occurs because the lack of time parents at homecaused by activities and busy parents outside the home while working. Therefore,researchers feel the need to analyze the social skills of students who viewed from thework of parents. Objective: To know the description of student communication skillseen from status of work of parent. 2) To know the description of students' humor skillsseen from the status of the parent's job. 3) To know the description of student friendshipskills seen from the status of parent work. 4) To know the description of role skills inthe student group viewed from the status of the parent's job. 5) To know the descriptionof the polite skills in the student association seen from the status of parent work 6) Toknow the description of social skills of students seen from the status of the parent's job.This research uses descriptive quantitative method. Data collection techniques usedquestionnaires. To analyze data using percentages. Subjects in this study were 228students. The results of this study are: Student social skills seen from the status ofparent work are both in the skilled category, although the percentage of social skills ofstudents whose father works as a contractor and his mother works as a lecturer higherthan the parents who work as doctors, civil servants, employees and So with thepercentage of contractor father 60% and lecturer 85.7%. But the difference is not seensignificantly, because junior high school students are still in early adolescentdevelopment stage.Keywords: Social Skills, Job Status